1990
DOI: 10.1117/12.19660
|View full text |Cite
|
Sign up to set email alerts
|

<title>Task performance and contrast polarity on hard copy and video displays</title>

Abstract: Performance was measured on an editing task which required counting the number of occurrences of an assigned letter in a paragraph of random letters. The task was presented in three different display modes: (a) a video display (VDT) with white characters on a black background, (b) a white-on-black photograph of the VDT display, and (c) a black-on--white photograph of the VDT task display. The viewing conditions for the three display modes were matched. Defocus was introduced by cylindrical lenses (simulated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Limitations of the present study include the small sample size and the short task duration. While a significant increase in post‐task symptoms was observed, the finding of no significant change in reading speed with up to 2D of astigmatism is consistent with previous findings 14,15 . Indeed, a post‐hoc power analysis demonstrated that the sample size would have to be increased to over 174 subjects for the size of the change in reading rate with induced astigmatism observed here to become significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Limitations of the present study include the small sample size and the short task duration. While a significant increase in post‐task symptoms was observed, the finding of no significant change in reading speed with up to 2D of astigmatism is consistent with previous findings 14,15 . Indeed, a post‐hoc power analysis demonstrated that the sample size would have to be increased to over 174 subjects for the size of the change in reading rate with induced astigmatism observed here to become significant.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to the observations of Sheedy et al. 14 Their investigation examined the effect of up to 1.50D of induced astigmatism (minus axis 90°) on task performance during an editing task which required counting the number of times an assigned letter occurred in a paragraph of text. They also compared hardcopy printed text having either a black‐on‐white or white‐on‐black polarity with a computer screen having a white‐on black display.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…115 A significant reduction in task performance of a computer based editing task (increased task completion time and number of errors) was also found to occur with 1.50 D of induced astigmatism. 116 These findings indicate that uncorrected astigmatism has the potential to impact a number of different common occupational visual tasks, particularly tasks with a high acuity demand.…”
Section: Functional Impact Of Astigmatismmentioning
confidence: 94%